Tics en procesos de enseñanza y aprendizaje: caso Marcel Laniado de Wind en Machala. - De La Cruz Delgado, Jorge Jossemar (My University, 2019)
The research addresses the insertion of ICTs in academic processes such as the Principle and Marcel Laniado de Wind Educational Unit of an official nature. The study focuses on exploring applications that support the academic teaching and learning processes through educational social networks, such as Edmodo & Socrative. Consequently, the application of these programs will improve the interaction between teachers, students and parents, since it is possible to generate multimedia content, presentations, tutorials, manage activities and communication. This functionality facilitates academic performance in students, minimizes the difficulty of learning in terms of style and rhythm, as well as the exploratory capacity for both teachers and students.
La investigación aborda la inserción de las TICs en los procesos académicos como es el caso de la Unidad Educativa Principito y Marcel Laniado de Wind de carácter oficial. El estudio se enfoca en explorar aplicaciones que sirvan de apoyo en los procesos de enseñanza y aprendizaje de la academia por medio de redes sociales educativas, tales como Edmodo & Socrative. En consecuencia, la aplicación de estos programas mejorará la interacción entre docentes, estudiantes y padres de familia, ya que es posible generar contenido multimedia, presentaciones, tutorias, gestionar actividades y comunicación. Esta funcionalidad facilita el rendimiento académico en estudiantes, minimiza la dificultad del aprendizaje en cuanto a estilo y ritmo, como también la capacidad exploratoria tanto para docentes y estudiantes.
Keywords: TICS; WEB 2.0; MARKETING DIGITAL; EDMODO; SOCRATIVE